Numerical Modelling for the Effect of Metal-mould Air Gaps on Shell Thickness in Horizontal Continuous Casting of Cast Iron - A. Chawla; N.S. Tiedje; J. Spangenberg (Archives of Foundry Engineering, 2023)
This paper presents a numerical model for the horizontal continuous casting of cast iron (HCCCI). A computational three-dimensional (3D) steady-state, coupled with fluid flow and heat transfer simulation model was developed and validated against experimental results to study the shell thickness and solidification of ductile cast iron. The study introduces the influence of an air gap at the melt-mould interface, which has long been known to have a detrimental effect on the efficiency of the process. The effect of the length and thickness of the melt-mould air gaps (also referred to as top air gaps) on solidification and remelting of the solid strand is studied. Parametric studies on top air gaps suggested a substantial effect on the solid and eutectic area at the top-outlet end of the die when the length of air gas was varied. This study serves to create a foundational and working model with the overall objective of process optimisation and analyzing the effect of operating process input parameters on the shell thickness of the strand.